Cluster-based metal–organic frameworks as sensitive and selective luminescent probes for sensing nitro explosives. (3rd August 2015) - Hu, Xiao-Li; Qin, Chao; Wang, Xin-Long; Shao, Kui-Zhan; Su, Zhong-Min
Abstract : Employing a C 3 symmetric ligand, one new cluster-based MOF [Cd2.5 Na(NTB)2 (DMF)4 ]·3DMF (1 ) has been successfully obtained. The results reveal that compound1 could be applied as a fluorescence sensor for TNP with high sensitivity and selectivity. Abstract : One new cluster-based metal–organic framework, namely, [Cd2.5 Na(NTB)2 (DMF)4 ]·3DMF (1 ) (NTB = 4, 4′, 4′′-nitrilotrisbenzoic acid; DMF = N, N -dimethylformamide) has been successfully obtained by employing a C 3 symmetric ligand. In1, the NTB links two different metal centers (single metal and Cd3 cluster) to form two kinds of 1D chains, which linked through the carboxylate O atom of the NTB ligand to give rise to a 3D framework. Moreover, desolved1 can be well dispersed in different solvents, which demonstrate distinct solvent-dependent luminescence spectra with emission intensities significantly quenched toward nitrobenzene (NB) and 2, 4, 6-trinitrophenol (TNP). The results reveal that1 could be applied as a fluorescence sensor for TNP with high sensitivity and selectivity.